Pharmacist-led medication reconciliation service for patients after discharge from tertiary hospitals to primary care in Singapore: a qualitative study - Griva, Konstadina (2024)
Background: Medication discrepancies commonly occur when patients are transferred between care settings. Despite the presence of medication reconciliation services (MRS), medication discrepancies are still prevalent, which has clinical costs and implications. This study aimed to explore the perspectives of various stakeholders on how the MRS can be optimized in Singapore. Methods: This is a descriptive qualitative study. Semi-structured interviews with 30 participants from the National Healthcare Group, including family physicians (N = 10), pharmacists (N = 10), patients recently discharged from restructured hospitals (N = 7) and their caregivers (N = 3) were conducted. All transcribed interviews were coded independently by three coders and inductive thematic analysis approach was used. Results: Five core themes were identified. (1) The MRS enhanced healthcare services in various aspects including efficiency and health literacy; (2) There were several challenges in delivering the MRS covering processes, technology and training; (3) Issues with suitable patient selection and follow-up; (4) Barriers to scaling up of MRS that involve various stakeholders, cross-sector integration and environmental restrictions; and finally (5) Role definition of the pharmacist to all the stakeholders. Conclusion: This study identified the role of MRS in enhancing healthcare services and explored the challenges encountered in the provision of MRS from family physicians, pharmacists, patients and their caregivers. These findings supported the need for a shift of MRS towards a more comprehensive medication review model. Future improvement work to the MRS can be conducted based on the findings.